Prevalence, risk factors, and impact on clinical outcome of extended-spectrum beta-lactamase-producing Escherichia coli bacteraemia: a five-year study. (October 2015) - Denis, B.; Lafaurie, M.; Donay, J.-L.; Fontaine, J.-P.; Oksenhendler, E.; Raffoux, E.; Hennequin, C.; Allez, M.; Socie, G.; Maziers, N.; Porcher, R.; Molina, J.-M.
Graphical abstract: Highlights: ⿢ The prevalence and impact of ESBL Escherichia coli bacteraemia was investigated, with a focus on patients with haematological diseases. ⿢ A dramatic increase in the prevalence of ESBL-EC bacteraemia was identified. ⿢ On multivariate analysis, a risk factor for ESBL-EC bacteraemia was found to be previous ESBL-EC colonization. ⿢ ESBL-EC bacteraemia was not associated with a prolonged length of hospital stay. ⿢ Despite more inadequate initial antimicrobial treatment, mortality was not significantly increased. Summary: Background: The impact of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli (ESBL-EC) bacteraemia on outcome remains controversial. Methods: A retrospective analysis of the prevalence, risk factors, clinical features, and outcomes of all ESBL-EC bacteraemia in one French hospital over a 5-year period was performed. A case⿿control study was undertaken: cases had at least one ESBL-EC bacteraemia and controls a positive non-ESBL-EC bacteraemia. Results: The prevalence of ESBL-EC bacteraemia increased from 5.2% of all positive E. coli blood cultures in 2005 to 13.5% in 2009 ( p < 0.003). CTX-M represented 70% of ESBL-EC bacteraemia strains, and strains were not clonally related. On adjusted analysis, the only significant risk factor for ESBL-EC bacteraemia was a previous ESBL-EC colonization (odds ratio 11.3, 95% confidence interval 1.2⿿107; p = 0.003). Initial antimicrobial therapy was less frequently adequate in the ESBL-EC group (48% vs. 85%; p = 0.003). The presence of ESBL-EC bacteraemia was not associated with a longer hospital stay ( p = 0.088). Day 30 mortality was high, but not significantly different in the two groups (30% vs. 27%; p = 0. 82). Conclusion: The prevalence of ESBL-EC bacteraemia has been increasing dramatically. Previous colonization with ESBL-EC was a strong risk factor for ESBL-EC bacteraemia. More inadequate initial antimicrobial therapy was noted in the ESBL-EC group, but mortality and length of hospital stay were not significantly different from those of patients with non-ESBL-EC bacteraemia.